EXPLORING THE VIABILITY AND IMPACT OF VEGANISM IN LUXURY FASHION - Sharma, Neha; Mayank , Kumar Rahul; Azahruddin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
As environmental concerns rise, luxury fashion brands are increasingly adopting vegan materials to create eco-friendly collections without compromising on quality or style. This study aims to explore the viability and impact of veganism in luxury fashion, focusing on its influence on consumer behavior, industry standards, and sustainability. A comprehensive review of secondary sources, including academic literature, industry reports, and sustainability assessments, was conducted to analyze the rise of vegan materials in luxury fashion. The study found that environmental awareness, ethical consumerism, and technological advancements are key drivers behind the increasing viability of vegan materials like Piñatex and Mylo in luxury fashion, despite challenges related to durability and environmental trade-offs. The adoption of vegan materials offers luxury brands a strategic opportunity to align with consumer demand for sustainability and ethical production, enhancing brand image and loyalty. Future research should explore the scalability of vegan materials, examine consumer perceptions of vegan luxury, and assess the long-term sustainability and lifecycle impacts of these alternatives.